Living Together and Christian Ethics - Thatcher, Adrian (Cambridge, UK ; New York Cambridge University Press, 2002)
Living Together and Christian Ethics is the first positive, in-depth study of cohabitation outside marriage from a mainstream Christian theological perspective. The book retrieves the traditions of betrothal from the Bible and church history, and shows
Keywords: Unmarried couples -- Religious aspects -- Christianity. Betrothal -- Religious aspects -- Christianity. Marriage -- Religious aspects -- Christianity